Fe-Allocation in Liver during Early Stages of Endotoxemia in Fe Overload Rats - Rousseau, Iván (2011)
The hypothesis of this study was that alterations in Fe distribution triggered by lipopolysaccharide (LPS) administration were affected in vivo by Fe overload. Lipopolysaccharide treatment by itself significantly decreased Fe content in serum and increased the blood NO-hemoglobin (NO-Hb) EPR signal and nitrotyrosine protein content in liver, as compared to values in control animals. Fe overload (produced by Fe-dextran ip administration) caused an increase, as compared to values in control animals, in Fe content in serum, and a significant enhancement in ferritin (Ft) content, Fe content in Ft, the labile Fe pool (LIP), and the protein carbonyl content in the liver. The simultaneous administration of LPS and Fe-dextran lead to a significant increase in the Fe content in serum, blood NO-Hb EPR signal, the content of Fe, Fe in Ft, LIP, protein carbonyl, and nitrotyrosine protein in liver, as compared to values in control animals. The data reported here indicate that the protective strategy against endotoxemia of sequestering serum Fe content is not fully operative under Fe overload conditions. However, the oxidative condition of the liver does not seem to be being affected, since endogenous mechanisms were able to regulate the amount of catalytically active Fe to the same levels observed after Fe-dextran administration, even in the presence of LPS, over the initial six-hour period.